Factors that Determine Work Precariousness - The comparison between the National and Foreign Direct Investment Industries:The case of Celaya Guanajuato México - Alvarez Orozco, Dolores Guadalupe; Ojeda, José Felipe; Lopez Mateo, Celina (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
In 2012, the reform of the Federal Labor Law was implemented in Mexico, arguing that it was necessary to make the legislation more flexible, in order to position Mexico as a viable country to attract Foreign Direct Investment (FDI). However, there has been little monitoring on the real effects of these changes. The objective of this research was to analyze the factors that determine the precarious working conditions in the city of Celaya Guanajuato Mexico with the use of a quantitative approach of a non-experimental cross-sectional design. The results identified that precarious working conditions are correlated with the gender, age, schooling, economic sector and origin of the investment. The implications for management are: The legal flexibility for attracting direct foreign investment according to this research, has been an appropriate strategy, since it pressures labor markets to improve their conditions to be competitive, because the industry with direct foreign investment is governed by the Law, on the other hand, the national industry reflects labor practices well below the legal minimums.